Circumstances of death in sudden death in epilepsy: interviews of bereaved relatives. Issue 3 (1st March 1998) - Nashef, L; Garner, S; Sander, J W A S; Fish, D R; Shorvon, S D
Abstract : OBJECTIVES: To study the circumstances of death in sudden death in epilepsy. METHODS: Self referred bereaved relatives of patients with epilepsy who had died suddenly were interviewed with information obtained substantiated through other sources—namely, coroners' officers' reports, postmortem reports, previous medical records, and EEG reports. RESULTS: Of 34 cases, 26 were classified as sudden unexpected deaths in epilepsy (SUDEP). Twenty four of 26 cases of SUDEP were unwitnessed. Evidence indicative or suggestive of a seizure was found in most. In 11 of 26 the position of the head was such that breathing could have been compromised. Cases included both localisation related and idiopathic primary generalised epilepsy. Only three were in remission at the time of death. Most relatives expressed the view that they would have preferred to have known that epilepsy could be fatal. CONCLUSIONS: Although the deaths in question were largely unwitnessed, the available evidence suggested that most cases of SUDEP represented ictal or postictal seizure deaths, occurring in people with a history of generalised tonic clonic seizures, and in both primary generalised and localisation related epilepsy. These interviews highlight the needs of bereaved relatives and their sense of isolation in the face of an entirely unexpected and apparently unexplained loss.